Pengaruh Pengetahuan, Sosialisasi, Pelayanan, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi yang Melakukan Pekerjaan Bebas Tahun 2020 - Pebriani, Reny Aziatul; RM. Rum Hendarmin (Jurnal Ilmiah Wahana Akuntansi, 2021)
This study aims to investigate the effect of knowledge, socialization, service, and tax sanctions on individual taxpayer compliance at the notary office in Palembang. The data used are primary and secondary data with data collection techniques through literature study, observation, interviews, and distributing questionnaires to 50 respondents. The data analysis technique used multiple linear regression. Further statistical tests prove knowledge, socialization, and service have a significant effect on tax compliance variables. However, tax sanctions are not proven to have a positive effect on tax compliance. This research provides benefits to tax agencies to improve taxpayer compliance through knowledge, socialization, and service.